Between seeing and living : a series of landscape interventions for enhancing the living heritage of Arniston/Waenhuiskrans - Prinsloo, Johan Nel (University of Pretoria, 2021)
Mini Dissertation (ML (Prof))--University of Pretoria, 2020.